Austenitic Steel AISI 304 under Static and Cyclic Loading - Chvalnikova, Veronika; Uhricik, Milan; Palcek, Peter; Slezak, Martin; Sikyna, Lukas; Drimalova, Petra (Manufacturing Technology Journal, 2023)
Austenitic steels are among the most widely used materials in industries such as automotive, food, energy, chemical, etc. They are mainly used due to properties such as corrosion resistance, good strength, hardness, or weldability. Microstructural analysis was performed on a light microscope Neo-phot 32. AISI 304 austenitic steel has a microstructure formed by a large number of polyhedral austenite grains of different sizes. The steel microstructure, mechanical and fatigue properties, and areas of the plastic zone after the bending impact test were investigated. The surface hardness of samples was measured on a Zwick Roell ZHVμ microhardness measuring device using the Vickers method. After the bending impact test, fractures were formed with a significant deformation with a typical dimple morphology. The fatigue test, performed on a Zwick Roell resonant pulsator, monitored the plastic deformation causing changes in mechanical properties. Finally, fractographic evaluations of the fracture surfaces were performed on a Tescan Vega LMUII. scanning electron microscope.
Keywords: Austenitic steel; Crack; Fracture; Static loading; Cyclic loading